Global Vegetation and Land Surface Dynamics in a Changing Climate - Mondal, Pinki; McDermid, Sonali Shukla; Mondal, Pinki; McDermid, Sonali Shukla (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Global ecosystem changes are influenced by a combination of natural and anthropogenic factors. Ongoing changes in rainfall, temperature, and carbon dioxide in the atmosphere can affect natural or managed vegetation, such as forest, grassland, or farmland. Moreover, anthropogenic pressures, such as forest clearing, cattle grazing, increasing infrastructural development, intensive management, and expansion of cropland, can contribute to ecosystem degradation. This collection presents a wide range of studies examining natural and anthropogenic drivers in diverse ecosystems in Africa, Asia, and North America.
English
Keywords: Research & information: general; solar-induced chlorophyll fluorescence; drought; photosynthesis; East Africa; water stress; NDVI; climate change; perceived impact of climate change; climate change adaptation; ordered probit regression; determinants of climate change impact; adaptive capacity; climate change vulnerability; exposure; resilience; sensitivity; vegetation; conservation; fire; grazing; savanna; woody vegetation; vegetation activity; vegetation anomaly; random forest; n/a